TOKOH SRI SUMARAH KARYA UMAR KAYAM SUATU KAJIAN BUDAYA JAWA - Ni Ketut Sukiani; Gusti Ayu Made Rai Suarniti; Ni Made Suwendri; Ida Bagus Astika Pidada (Universitas Warmadewa, 2024)
This research analyzes the character Sri Sumarah by Umar Kayam (A Study of Javanese Culture). Through the characters in Sri Sumarah, this research aims to describe and discover aspects of Javanese cultural values, especially in wayang characters. The method used in this research is a qualitative method with analytical descriptive analysis. Primary sources were obtained from library research in the form of the novel Sri Sumarah by Umar Kayam (1995) and secondary sources were also used through relevant literature reviews. The approach used to explain characterization in Sri Sumarah's literary works is a structural approach related to intrinsic structure including theme, incident, character, plot, language style, story technique and composition. The extrinsic structure includes historical, sociological, psychological, religious and philosophical aspects. Based on the results of the analysis, it shows that Sri Sumarah is a Javanese woman with a strong and resilient personality in facing various life problems. He is depicted as a figure who places Subadra and Kunti as role models. For almost all his life, Sri Sumarah played a very dominant role over the two puppet characters. The characters in Sri Sumarah succeed in presenting a strong characterization structure as described by the author.